Pengaruh Polyurethan pada Kemampuan Meredam Suara Home Made Foam: Riki Perdana, Tri Utami, Erlin Eveline, Devi Afriani, dan Suparno - Riki Perdana Riki Perdana; Tri Utami Tri Utami; Erlin Eveline Erlin Eveline; Devi Afriani Devi Afriani; Suparno Suparno (Jurnal Fisika dan Aplikasinya, 2019)
Effective foam composition has been produced as sound absorbing material based on sound absorption coefficient value. The method used is experimentation, by mixing the main ingredients (polyurethane) with the developer liquid (isocyanate). There are five variations of research, with the isocyanate as a control variable. The results obtained from the first to fifth variations in a row are 0.152; 0.072; 0.042; 0.028 and 0.056. From the findings it can be concluded that the less polyurethane is added the greater the absorption coefficient value so it is better to absorbs the sound.